The demographic, psychosocial and clinical characteristics associated with cardiac risk factor control: an analysis of secondary prevention in adults with established coronary heart disease. (11th May 2022) - Brennan, S; Avalos, G; Mc Evoy, J W
Abstract: Funding Acknowledgements: Type of funding sources: None. Background and Purpose: Achieving risk factor (RF) control in patients with established coronary heart disease (CHD) reduces the risk of CHD events.(1) Cross-sectional studies have shown that the implementation of current prevention guidelines is poor, with most patients failing to meet recommended targets.(2, 3) This study aims to identify demographic, psychosocial and clinical characteristics associated with the non-achievement of RF targets in a population with CHD. Methods: In this post-hoc cross-sectional analysis, multivariable logistic regression identified characteristics significantly associated with poor RF control in participants of the iASPIRE study which recently assessed secondary CHD prevention in Ireland. Results: An unhealthy diet (Odds Ratio [OR] 1.6, 95% CI 1.1-2.4, p=0.015), male sex (OR 1.8, 95% CI 1.2-2.8, p=0.007) and type of acute coronary syndrome event (OR 0.6, 95% CI 0.4-0.9, p=0.012) were associated with failure to achieve blood pressure recommendations. Female sex (OR 2.3, 95% CI 1.4-3.8, p=0.002), lack of high-intensity statin (OR 2.4, 95% CI 1.5-3.8, p<0.001) and recurrent hospitalisation for CHD (OR 1.9, 95% CI 1.3-2.8, p=0.001) were associated with poor LDL-C control. Decreasing age (OR 0.9, 95% CI 0.9-1.0, p=0.018), marriage (OR 4.3, 95% CI 1.5-12.1, p=0.007) and insulin use (OR 9.7, 95% CI 1.9-50.4, p=0.007) were associated with a HbA1c of ≥53mmol/mol. The absence of a longstanding illness or disability and decreasing resting heart rate were associated with composite RF control. Conclusion: Several demographic, psychosocial and clinical characteristics are associated with achieving guideline-recommended RF targets. These findings will support the development of targeted solutions that will improve guideline implementation and the practice of CHD prevention in a high-risk population.